PENINGGALAN PERANG DUNIA II DAN DAMPAK TERHADAP BUDAYA MASYARAKAT PULAU WAKDE, KABUPATEN SARMI - Sonya M. Kawer (BALAI ARKEOLOGI PAPUA, 2012)
Research in Sarmi District East Coast West performed Wakde Island. That reveal the history of life during World War II through the remains-the remains contained in the Region. Wakde is an area that can be said to be a center of colonial activity that leaves traces the history and culture of the past, which are still visible physical form remains Based on the survey results illustrate that Wakde Island is one of the historic places once inhabited by Japanese soldiers and captured by Allied forces at the outbreak of the Pacific war.